1998
DOI: 10.1021/jp972966b
|View full text |Cite
|
Sign up to set email alerts
|

Computational Studies of Cyclobutadiene and Benzocyclobutene Fused to p- and o-Quinone

Abstract: Cyclobutadiene and benzocyclobutenes fused to o- and p-quinone have been studied by computational methods. Geometries were optimized at the B3LYP/6-31G* level, and absolute NMR shielding values were calculated using the GIAO method with the HF/6-31G* basis set. NICS values of the compounds 8b,c and 9b,c indicate strong antiaromatic character for cyclobutadiene units. However, 8a and 9a show negative NICS values where the quinodal system reduces the antiaromaticity significantly by forcing these systems to poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 29 publications
2
19
0
Order By: Relevance
“…[11] suggested that isomers 5 a and 5 b might be capable of existing. However, a subsequent CASPT2(10,10)//GVB(2) study revealed that structure 5 a was more stable than structure 5 b by 5 kcal mol…”
mentioning
confidence: 99%
“…[11] suggested that isomers 5 a and 5 b might be capable of existing. However, a subsequent CASPT2(10,10)//GVB(2) study revealed that structure 5 a was more stable than structure 5 b by 5 kcal mol…”
mentioning
confidence: 99%
“…However, these analyses must be conducted under the same experimental conditions; i.e., pH, cone potential and capillary energy, because signal suppression can occur . Thus, sequential MS is necessary to describe which isomer is being analyzed . In this context, ESI‐MS/MS analysis can help elucidate the fragmentation mechanism for each compound, and the structure of an unknown compound of this class can be suggested .…”
Section: Resultsmentioning
confidence: 99%
“…). Comparison of the properties (reactivity, protonation, and dissociation) of ortho ‐naphthoquinone and para ‐naphthoquinone provides information about how conjugation affects these systems and more complex quinonoid moieties …”
mentioning
confidence: 99%
“…[1] Even though the parent benzocyclobutadiene A (Figure 1) readily dimerizes,e ven at temperatures as low as 75 K, [2] A can still be observed by fast-flow NMR spectroscopy techniques. [3] Thei ntroduction of sterically demanding substituents allowed the isolation of benzocyclobutadienes B-D. [4][5][6] According to these experimental and theoretical studies, [7] the diamagnetic ring current on the benzene rings of the benzocyclobutadienes is reduced owing to the paramagnetic ring current of the fused cyclobutadiene moieties. Progress in main-group-element chemistry has meanwhile enabled the incorporation of heavier Group 14 elements into neutral cyclobutadienes and their charged (dianionic and dicationic) derivatives.…”
Section: Benzannulated Cyclobutadienes (Benzocyclobutadienes)mentioning
confidence: 99%